Pemikiran Buya Hamka tentang Aliran Kebatinan di Indonesia dan Implikasinya bagi Masyarakat Indonesia - M. Kharis Majid; Muttaqin; Asep Awaludin; Farhah; Hifdzi Syahril Mawardi (Civil Officium: Journal of Empirical Studies on Social Science, 2025)
This study aims to examine Buya Hamka's views on the spread of mystical beliefs (kebatinan) in Indonesia and their implications for Indonesian society. The research employs a qualitative method with a descriptive-analytical and sociological approach. Data were collected through library research of Buya Hamka’s works and other related scholarly sources, then analyzed systematically to reveal his interpretation of kebatinan and his critical response to its development. The study was conducted within Universitas Darussalam Gontor's academic environment without involving direct field respondents. The results indicate that, according to Hamka, kebatinan stems from the Arabic concept of “bathin” and is derived from the deviant sect of Bathiniyyah within Islamic tradition. Hamka argued that kebatinan has spread extensively, particularly in Java, and has significantly contributed to the ambiguity of religious identity, promoted syncretism, and led to the distortion and denigration of Islamic teachings. The study concludes that Hamka’s perspective represents a critical theological and sociological stance, urging the Muslim community to safeguard the purity of Islamic teachings from heterodox local influences